2014
DOI: 10.1039/c3cp54894e
|View full text |Cite
|
Sign up to set email alerts
|

Introducing manganese complexes as redox mediators for dye-sensitized solar cells

Abstract: The abundance and low toxicity of manganese have led us to explore the application of manganese complexes as redox mediators for dye sensitized solar cells (DSCs), a promising solar energy conversion technology which mimics some of the key processes in photosynthesis during its operation. In this paper, we report the development of a DSC electrolyte based on the tris(acetylacetonato)manganese(iii)/(iv), [Mn(acac)3](0/1+), redox couple. PEDOT-coated FTO glass was used as a counter electrode instead of the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 50 publications
2
40
0
1
Order By: Relevance
“…Properties of metal(III) β-diketonato complexes [M(R 1 COCHCOR 2 ) 3 ], M = metal and R = pendant β-diketonato side groups such as CH 3 , have been studied with a variety of different techniques including crystallography [1], electrochemistry [2], non-linear refractive measurements [3], UV-Vis spectroscopy [4], and high frequency electron paramagnetic resonance (EPR) [5]. However, characterization of these complexes by means of X-ray photoelectron spectroscopy (XPS) is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Properties of metal(III) β-diketonato complexes [M(R 1 COCHCOR 2 ) 3 ], M = metal and R = pendant β-diketonato side groups such as CH 3 , have been studied with a variety of different techniques including crystallography [1], electrochemistry [2], non-linear refractive measurements [3], UV-Vis spectroscopy [4], and high frequency electron paramagnetic resonance (EPR) [5]. However, characterization of these complexes by means of X-ray photoelectron spectroscopy (XPS) is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Chenodeoxycholic acid (1) has been used as an electrolyte additive in n-type DSSCs to decrease interfacial chargerecombination reactions through passivation of the TiO 2 surface. [14] Salvatori et al concluded that molecules of 1 achieve this by forming supramolecular aggregates on the TiO 2 surface, thereby limiting the access of reduced species in the electrolyte. [15] In this study, the addition of 1 increased the J SC value from 6.95 AE 0.20 mA cm À2 to 7.65 AE 0.39 mA cm À2 and the V OC value from 595 AE 6 mV to 645 AE 12 mV (see Table S1 and Figure S6).…”
mentioning
confidence: 99%
“…However, the disadvantage of the organic redox couples is their inferior stability. The third type of redox couples is metal complexes with different valence states containing iron (Fe), copper (Cu), nickel (Ni), manganese (Mn), vanadium (V), and/or cobalt (Co) . As promising alternatives to the iodide redox couple, the metal complexes have the merits of a weak absorption of visible light, weak corrosion of metal electrodes, and adjustable redox potentials.…”
Section: Carbon Counter Electrode In the Dye‐sensitized Solar Cellmentioning
confidence: 99%
“…The third type of redox couples is metal complexes with different valence states containing iron (Fe), copper (Cu), nickel (Ni), manganese (Mn), vanadium (V), and/ or cobalt (Co). [56][57][58][59][60][61][62][63] As promising alternatives to the iodide redox couple, the metal complexes have the merits of a weak absorption of visible light, weak corrosion of metal electrodes, and adjustable redox potentials. However, their complicated synthesis and purification processes lead to high costs.…”
Section: Types Of Redox Couples For the Counter Electrodementioning
confidence: 99%